Doing philosophy for wisdom in Islamic Education - Wan Yusoff, Wan Mazwati; Hashim, Rosnani (IIUM Press, 2022)
The purpose of this book is to argue for the inclusion of philosophy into the curriculum of Muslim education to achieve wisdom.